SCARCITY OF WATER IN THE TWENTY-FIRST CENTURY: PROBLEMS AND POTENTIAL REMEDIES - Faisal Abass Padder; Asif Bashir (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
ABSTRACT The scantiness of water is a pressing global riddle that pertains to the inadequate availability of enough safe and clean water resources to fulfill human and ecological requirements. It emerges as a result of various factors such as population growth, climate change, pollution, ineffective water management, and unsustainable water usage practices. This summary offers an overview of the issue and highlights possible remedies. These solutions encompass actions like conserving water, collecting rainwater, improving irrigation methods, treating and reusing wastewater, employing desalination techniques, investing in water infrastructure, managing groundwater resources, establishing fair water pricing and governance, fostering public awareness and education, and fostering international cooperation. By implementing these strategies, we can address water scarcity and advance sustainable water management for the benefit of present and future generations.